The Effect of Cooperative Learning on Students’ Writing Skills in Indonesian Language Learning for IV Grade Elementary School Students - Minyarahmah; Waridah (Educia Journal, 2026)
Writing is a fundamental language skill that supports students’ ability to communicate ideas, construct knowledge, and achieve academic success. However, many elementary school students continue to experience difficulties in generating ideas, organizing paragraphs, and expressing thoughts effectively in written form. This study aimed to examine the effect of the Think Talk Write (TTW) cooperative learning model on the writing skills of fourth-grade students at SDN 11 Sengkuang Bora, Melawi Regency, West Kalimantan. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 22 fourth-grade students selected through total sampling. Data were collected through writing tests administered before and after the implementation of the TTW model. Students’ writing performance was assessed based on content, organization, vocabulary, language use, and mechanics. The collected data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test with the assistance of IBM SPSS Statistics Version 27. The results revealed that students’ mean writing score increased from 62.77 in the pretest to 77.95 in the posttest, indicating an improvement of 15.18 points. The normality test confirmed that both datasets were normally distributed, with significance values greater than 0.05. Furthermore, the paired-sample t-test produced a significance value of 0.000, which was lower than the 0.05 significance level. These findings indicate that the Think Talk Write learning model had a significant positive effect on students’ writing skills. The study concludes that TTW is an effective instructional strategy for enhancing elementary students’ writing achievement by promoting active thinking, collaborative discussion, and structured writing practices.